Patient Safety Culture Among Healthcare Settings in Low and Middle-Income Countries: A Systematic Review and Meta-Analysis - Natnael Atnafu Gebeyehu; Kirubel Tegegne; Biruk Admass; Nathan Shewangashaw; Yibeltal Atalay; Dagne Sewuyew; Awoke Gebremariam; Kelemu Abebe Gelaw (Patient Experience Journal)
Ensuring patient safety is a crucial element in providing high-quality healthcare services. Therefore, this study aimed to assess the current state of patient safety culture in healthcare settings within low- and middle-income countries. A thorough search was conducted across multiple databases, including Science Direct, Scopus, Google Scholar, EMBASE, and PubMed. Data extraction was carried out using Microsoft Excel, and statistical analysis was performed using STATA software (version 14). To evaluate publication bias, methods such as Egger's regression tests, rank tests, and forest plots were utilized. The I2 statistic was used to assess heterogeneity, followed by an overall estimated analysis. Additionally, subgroup analyses were performed based on sample size and type of healthcare. After reviewing 1,143 articles, 21 publications involving 17,782 research participants were selected. The results indicated that the prevalence of patient safety culture in healthcare facilities in low- and middle-income countries was 48.25 percent (95 percent CI: 41.26, 55.24), with an I2 value of 78.8 percent. Among the various dimensions of patient safety culture, teamwork within units received the highest score (67.8%), while non-punitive responses to errors received the lowest score (27.6%). Compared to previous studies, it can be concluded that patient safety cultures in low- and middle-income countries are lacking, underscoring the need for targeted interventions to address this issue.